Ultrasonic Patterns of Benign Skin Formations - M. A. Bizunova; Yu. M. Krinitsyna; V. V. Onipchenko; E. S. Nedvigina; A. V. Taganov; I. G. Sergeeva (Vestnik Dermatologii i Venerologii, 2018)
Objective: to reveal ultrasonic features of of epithelial, dermal and vascular benign skin formations. Materials and methods. An ultrasonic study of 50 acantholytic nevuses, 50 acrochordons and 30 hemangiomas, which have an unambiguous clinical and dermatoscopic pattern and do not require differential diagnosis, was carried out. For the comparative evaluation of ultrasonic thickness and density of skin the ratio of scan indices in the lesion area relative to the indices in the adjacent healthy area of the skin was introduced. Results. On the scans of acantholytic nevus the formations that rose above the skin surface, with a nonuniform thickened, hyperechoic epidermis were visualized, in which hypoechoic round-shaped patches occur. A hypoechoic acoustic shadow was determined under the epidermis. On the scans of acrochordons the formations on a narrow base, which were located above the skin surface were visualized. In the region of formations, a discontinuous contour of epidermis with predominantly hyperechogenic areas was determined. Within the formations, the structure of the dermis is heterogeneous with the alternation of normoechoic and hypoechoic areas. Beneath the formation an epidermis structurally similar to the healthy skin epidermis is determined on the level of skin surface under which hypoechoic zone is visualized, which is an acoustic shadow. On the scans of hemangiomas the formations were visualized that rose above the skin surface, with a distinct lateral delimitation from the surrounding tissues. In the area of formations, the epidermis is non-uniformly thickened than healthy skin, hyperechoic round-shaped areas are visualized. Non-uniformly hypoechoic irregulary-shaped regions were determined in the dermis. Conclusion. All examined formations differ from healthy skin by increasing the thickness of the epidermis and dermis, as well as strengthening the overall acoustic solidity of the epidermis and decreasing the acoustic solidity of the dermis. The introduction of the ratio into practice makes it possible to quantify these changes. Moreover, each formation has a peculiar ultrasonic characteristic, allowing the use of pattern analysis for differential diagnosis between epithelial, dermal and vascular forms of benign skin formations.